STRATEGI MEMBANGUN KULTUR SEKOLAH YANG BERBUDAYA OLARAGA - Fransiskus Menggi; Fulgentius Meo Wea; Gabriel Alexandro Kadu; Bernabas Wani (Cermat : Jurnal Cendekiawan dan Riset Multidisiplin Akademik Terintegrasi, 2026)
This study aims to analyze strategies in building a sports-oriented school culture to enhance the interest and participation of high school students in sports activities. The research employed a qualitative approach, using data collection techniques such as in-depth interviews, participatory observation, and focus group discussions (FGD) with students, physical education teachers, school principals, and parents. The results showed that the main factors influencing students' interest and participation in sports include adequate sports facilities, the active role of physical education teachers, diverse sports programs, parental support, and a supportive school environment. Schools with well-maintained and complete sports facilities, as well as offering a variety of sports, both competitive and recreational, tend to have higher participation rates. Additionally, parental support and school policies that promote sports activities also play a significant role in creating a positive sports culture. The study concludes that to build a sustainable sports culture, schools need to develop a holistic strategy, which includes providing adequate facilities, enhancing the quality of sports teaching, and involving parents and the community in supporting sports activities. It is hoped that the findings of this research can contribute to the development of more effective sports policies and programs in schools..